The Economic Value of Bioherbs Application in Commercial Feed in Broilers - Widharto Widharto; Desna Ayu Wijayanti (UNIVERSITAS ISLAM LAMONGAN, 2023)
The research was conducted to determine the application of bioherbs or other designations, namely vegetable ingredients that can be added to commercial feed in broiler chicken. As many as 60 day old chick of broilers were devided into 4 treatments, that is were given commercial feed without bioherbs (T-PK), were givenecommercial feed with papaya leaves flour as much as 2 % (T-DP), were givenecommercial feed with of noni leaves flour as much as 2 % (T-DM) and were givenecommercial feed with moringa leaves flour as much as 2 % (T-DK). The variables observed feed conversion, feed cost per gain and income over feed cost. Feed conversion is 2.6 (T-PK), 2.3 (T-DP), 2.4 (T-DM) and 2.4 g/head/day (T-DK), feed cost perggain is Rp. 20.696,0,- (T-PK), Rp. 19.837,5,- (T-DP), Rp. 21.912,0,- (T-DM) and Rp. 21.588,0,- (T-DK), and income over feed cost is Rp. 2.304,0,- (T-PK), Rp. 3.162,5,- (T-DP), Rp.1.088,0,- (T-DM) and Rp. 1.412,0,- (T-DK). The result showed that given commercial feed with papaya leaves flour can decrease of feed conversion,afeed cost per gain and increase of income over feed cost but given commercial feed with of Morinda citrifolia L. and Moringa oleifera leaves flour only able to decrease feed conversion, and have not been able to reduce feed cost perggain and increase incomemover feedmcost. Research conclusion is given commercial feed with papaya leaves flour can increase of income over feed cost but given commercial feed with Morinda citrifolia L. and Moringa oleifera leaves flour have not been able to increase ofoincomeaover feedicost in broilers.